Bempedoic Acid, the First-in-Class Oral ATP Citrate Lyase Inhibitor with Hypocholesterolemic Activity: Clinical Pharmacology and Drug–Drug Interactions - Nicola Ferri; Elisa Colombo; Alberto Corsini (Pharmaceutics)
Bempedoic acid is a new drug that improves the control of cholesterol levels, either as monotherapy or in combination with existing lipid-lowering therapies, and shows clinical efficacy in cardiovascular disease patients. Thus, patients with comorbidities and under multiple therapies may be eligible for bempedoic acid, thus facing the potential problem of drug–drug interactions (DDIs). Bempedoic acid is a prodrug administered orally at a fixed daily dose of 180 mg. The dicarboxylic acid is enzymatically activated by conjugation with coenzyme A (CoA) to form the pharmacologically active thioester (bempedoic acid–CoA). This process is catalyzed by very-long-chain acyl-CoA synthetase 1 (ACSVL1), expressed almost exclusively at the hepatic level. Bempedoic acid–CoA is a potent and selective inhibitor of ATP citrate lyase (ACL), a key enzyme in the biosynthetic pathway of cholesterol and fatty acids. The drug reduces low-density lipoprotein–cholesterol (LDL-C) (20–25%), non-high-density lipoprotein–cholesterol (HDL-C) (19%), apolipoprotein B (apoB) (15%), and total cholesterol (16%) in patients with hypercholesterolemia or mixed dyslipidemia. The drug has a favorable pharmacokinetics profile. Bempedoic acid and its metabolites are not substrates or inhibitors/inducers of cytochrome P450 (CYP450) involved in drug metabolism. On the other hand, bempedoic acid–glucuronide is a substrate for organic anion transporter 3 (OAT3). Bempedoic acid and its glucuronide are weak inhibitors of the OAT2, OAT3, and organic anion-transporting polypeptide 1B1 (OATP1B1) and 1B3 (OATP1B3). Thus, bempedoic acid could inhibit (perpetrator) the hepatic uptake of OATP1B1/3 substrate drugs and the renal elimination of OAT2 and OAT3 substrates and could suffer (victim) the effect of OAT3 transporter inhibitors, reducing its renal elimination. Based on these pharmacological characteristics, here, we describe the potential DDIs of bempedoic acid with concomitant medications and the possible clinical implications.